Efektivitas Model Pembelajaran Missouri Mathematics Project Terhadap Peningkatan Prestasi Belajar Matematika Siswa SMP - Asrina Rasli; Abdurahman Askois; Dian Lestari (Jurnal Akademik Pendidikan Matematika, 2022)
This research was a quantitative research by using experimental method with the research design were pretest-post test control grup design. Population in this research were all seventh grade students of SMP Negeri 8 Baubau in academic year 2021/2022. This research aimed to see the effectiveness of Missouri Mathematics Project (MMP) learning model in improving Mathematics learning achievement of seventh grade students in SMP Negeri 8 Baubau. Sample is this research was taken by using simple random sampling technique, namely class VIIA experimental class and VIIB as control class. The data collection in this research used an essay test, by using data analysis technique, they were descriptive analysis and inferential analysis. The result of inferential analysis by observing the normality test, there was a significant value of students’ Mathematics learning achievement in the experimental class 0,2 and the control class 0,079. While homogeneity test showed that the value of students’ achievement in the class was 0,178 . So that, it could be concluded that the two classes were normality distributie and homogeneus. The by using the t-test, it was known that tcount = 10,230 and significant at = 0,000<0,05, thus H0 was rejected. So that, Missouri Mathematics Project (MMP) learning model was effective in improving students’ achievement.